1997
DOI: 10.1063/1.365362
|View full text |Cite
|
Sign up to set email alerts
|

The binding energies of shallow donor impurities in GaAs quantum-well wires under applied electric fields

Abstract: Using a variational procedure, within the effective mass-approximation, we calculate the binding energy of a shallow-donor impurity in a rectangular cross-sectional area of a GaAs quantum-well wire, under the action of an electric field applied perpendicular to one of the interfaces, assuming an infinite-confinement potential. We study the binding energy of the donor impurity as a function of the system geometry, the applied electric field, and the donor-impurity position. It was found that the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…These parameters are suitable in GaAs/Ga 1Àx Al x heterostructures with an Al concentration of xD0:3 [14,30]. We have assumed the conduction-band discontinuity to be 56% of the total band gap difference between GaAs and Ga 1Àx Al x As, and the donor is located at the center of the wire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters are suitable in GaAs/Ga 1Àx Al x heterostructures with an Al concentration of xD0:3 [14,30]. We have assumed the conduction-band discontinuity to be 56% of the total band gap difference between GaAs and Ga 1Àx Al x As, and the donor is located at the center of the wire.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of studying the influence of an electric field on the binding energy, the state density, the polarizability have theoretical as well as technological relevance. The effect of an electric field, and the geometric form of the system on the binding energies of shallow-donor impurities in GaAs quantum-well wires was presented by several authors [14][15][16], considering an infinite confinement potential and using a variational scheme. Duque et al investigated the effect of an applied electric field on the binding energy, and polarizabilities of shallow-donor impurities implanted in rectangular cross-section GaAs-GaAlAs quantum-well wires [17], and in cylindrical GaAs low-dimensional systems [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been reported on the applied electric field and hydrostatic pressure dependencies of the shallow-donor-impurity and/or acceptor-impurity binding energies of the ground and first few excited states in QWW heterostructures [1][2][3][4]. The aim of the work reported in the present paper was to study the hydrostatic pressure and electric field effects on confined donor and acceptor impurities in transverse-rectangular section GaAs-(Ga,Al)As QWWs.…”
Section: Introductionmentioning
confidence: 96%
“…The influence of an electric field on the hydrogenic binding energy was presented by several authors [25][26][27][28][29][30][31][32]. The effect of an electric field and the geometric form of the system on the binding energies of shallow donor impurities in QWWs was presented by Montes et al [25,28] and Ulaş et al [26,27]. They found that the hydrogenic binding energy of a shallow donor impurity is a rather sensitive function of the geometry of the QWW and of the distribution of impurities inside the QWW.…”
Section: Introductionmentioning
confidence: 99%